Financial Literacy and Fintech Use on Financial Resilience: The Mediating Role of Financial Inclusion - Nyoman Trisna Herawati; Made Ary Meitriana; Ni Kadek Sinarwati (Universitas Warmadewa, 2026)
Financial resilience is a critical determinant of financial security. Teachers, as important figures in the educational landscape, endure substantial responsibilities in educating the new generation. Unfortunately, precarious socioeconomic conditions of teachers can undermine their professional performance. In turn, suboptimal financial management practices among educators can set a negative precedent, influencing students’ financial behaviors and attitudes. Addressing this research gap, the present study investigates the impact of financial literacy and the utilization of financial technology (fintech) on financial resilience, with financial inclusion acting as a mediating factor. This study applies the causality method to measure primary data through questionnaires with data collection techniques using google forms. A total of 116 high school teachers in Buleleng Regency with criteria determined by the researcher participated in this study. Data was analyzed using variant-based analysis of the Structural Equation Model (SEM) with Partial Least Square (PLS) version 3.0. The findings reveal that both financial literacy and fintech usage positively and significantly affect financial inclusion. Moreover, these variables, along with financial inclusion, exert a significant influence on financial resilience. Financial inclusion was also found to mediate the relationship between financial literacy and fintech use with financial resilience. The study highlights the importance of strengthening financial literacy and responsible fintech usage among teachers to enhance their financial resilience and long-term financial wellbeing. Additionally, financial inclusion plays a crucial supporting role in achieving financial resilience. This research enriches the existing literature by elucidating the roles of financial literacy, fintech use, and financial inclusion in shaping teachers' financial resilience.